Accumulation and release of Pb(II) in aqueous solution by aquatic mosses (Fontinalis antipyretica) - Martins, Ramiro (2010)
The uptake and release of Pb(II) by Fontinalis antipyretica was studied in laboratory, by exposing the plants to different lead concentrations for 144 h and 335 h contamination and decontamination periods, respectively. A first order kinetic model was fitted to the experimental data to determine the uptake and release constants, k1 and k2, and other relevant parameters. The metal accumulation capacity, at equilibrium, follows the order: Pb(II) > Zn(II) > Cd(II) > Cr(VI). A Bioconcentration Factor (BCF) and a Biological Elimination Factor (BEF) were also determined; for 0.9–2.2 mg Pb l–1, BCF decreases from about 30748 to 21296.